Supervisory and coworker support for safety: Buffers between job insecurity and safety performance of high-speed railway drivers in China. (August 2019) - Guo, Ming; Liu, Shuzhen; Chu, Fulei; Ye, Long; Zhang, Qichao
Highlights: We examine the effects of job insecurity and safety support on safety performance. Supervisory and Coworker Support for Safety are effective psychosocial resources. Interpersonal safety support can alleviate the negative impact of job insecurity. Survey data were collected from 470 high-speed railway drivers in China. Abstract: As job insecurity becomes increasingly common, seeking its palliatives has become a hot topic for scholars, especially for high-speed railway drivers who are vital for the development of China's high-speed railway. Researches have demonstrated that, organizational support is a valuable psychosocial resource that can alleviate individual negative behavior, yet its buffering effect between job insecurity and safety performance has attracted little attention. In this study, organizational support in the safety field was identified as supervisory and coworker support for safety. Using conservation of resources theory, this paper tested the predictive powers of job insecurity, supervisory support for safety, and coworker support for safety on safety performance. Additionally, it tested the buffer effects of both supervisory and coworker support for safety on the relationship between job insecurity and safety performance. The data were collected via questionnaires from 470 high-speed railway drivers in China. The results showed that (1) job insecurity had negative impact on safety compliance and safety participation; (2) higher safety support from the supervisor and coworker were associated with higher safety compliance and safety participation; (3) both supervisory and coworker support for safety moderated the effect of job insecurity on safety compliance and safety participation, respectively. Finally, theoretical as well as practical implications were proposed and suggestions for future research were also provided based on the findings in this study.